1967
DOI: 10.1136/bmj.4.5581.702
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of urinary tract infection in childhood based on examination of pared non-catheter and catheter specimens of urine.

Abstract: The accurate diagnosis of urinary tract infection. in infancy and childhood based on examination of the urine is made difficult by the number of variables involved. These include the age and sex of the patient, method of collection of the urine, time interval between micturition and urine examination, and technique of examination employed. The method of collection of urine is most important and for two common methodsplastic adhesive bags and midstream specimens-we have suggested diagnostic levels for cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…62 Combined with the studies identified by our previous reviews 56,116 this gives a total of six included studies for urine sampling, five primary studies and one systematic review for clinical signs and symptoms, and eight primary studies and one systematic review for dipstick testing (Figure 34). We identified a total of six studies that assessed urine sampling methods: four from the HTA review, [57][58][59][60] one from the BMJ paper 61 and one from our update searches. 62 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…62 Combined with the studies identified by our previous reviews 56,116 this gives a total of six included studies for urine sampling, five primary studies and one systematic review for clinical signs and symptoms, and eight primary studies and one systematic review for dipstick testing (Figure 34). We identified a total of six studies that assessed urine sampling methods: four from the HTA review, [57][58][59][60] one from the BMJ paper 61 and one from our update searches. 62 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared culture results from urine samples obtained by bag specimens with those obtained by catheter. 58,61 The appropriateness of a catheter specimen as the reference standard is questionable, meaning that these results are of limited value. One study compared culture of a nappy pad specimen with culture of SPA samples.…”
Section: Methods Of Urine Sampling In Primary Carementioning
confidence: 99%
See 3 more Smart Citations